PENINGKATAN VALUE ADDED BERBASIS KOMODITAS LOKAL DI DESA RENAH ALAI KECAMATAN JANGKAT PROVINSI JAMBI - Rosmeli Rosmeli; Emilia Emilia; Etik Umiyati; Nurhayani Nurhayani; Candra Mustika (Universitas Merdeka Madiun, 2022)
Renah Alai is one of the villages located in The District of Jangkat Jambi Province, The main livelihood of the villagers of Renah Alai is farmers, vegetables and tubers are the most widely grown crops. One of the plants that became the mainstay commodity in this village is Potatoes.The abundance of potato production is the main capital for the downstreaming of this commodity, The absence of potato products carried out by the community in the village of Renah Alai is an innovation that must be done, while the great potential in Potatoes is the initial capital in the downstreaming of potato products. The processing of potato cultivation is expected to keep the price of potatoes stable, the increase in community income, the opening of new jobs and the existence of - by the typical village of Renah Alai which is a tourist destination village.